GSK-3 mediates differentiation and activation of proinflammatory dendritic cells - Rodionova, Elena; Conzelmann, Michael; Maraskovsky, Eugene; Hess, Michael; Kirsch, Michael; Giese, Thomas; Ho, Anthony Dick; Zöller, Margot; Dreger, Peter; Luft, Thomas (Blood, 2007)
The key components of the intracellular molecular network required for the expression of a specific function of dendritic cells (DCs) are as yet undefined. Using an in vitro model of human monocyte-derived DC differentiation, this study investigates the role of glycogen synthase kinase 3 (GSK-3), a multifunctional enzyme critical for cellular differentiation, apoptosis, self-renewal, and motility, in this context. We demonstrate that GSK-3 (1) inhibits macrophage development during differentiation of DCs, (2) is constitutively active in immature DCs and suppresses spontaneous maturation, and (3) acquires a proinflammatory functional status mediating high levels of IL-12, IL-6, and TNF-α secretion, and partially inhibits IL-10 in the context of DC activation. In particular, GSK-3 enhances IL-12p35 mRNA expression and thus the production of the proinflammatory cytokine IL-12p70 by integrating the activities of other kinases priming GSK-3 targets and the inhibitory effects of Akt-1. GSK-3 may therefore act as a key integrator of activating and inhibitory pathways involved in proinflammatory DC differentiation and activation.
Prepublished online as Blood first edition paper, October 10, 2006
Gesehen am 26.10.2021